Polymeric alginate microspheres containing biochar to immobilize phosphate ions - Domingues, Murilo Teles [UNESP]; Bueno, Carolina de Castro [UNESP]; Watanabe, Cláudia Hitomi [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Loyola-Licea, Juan Carlos; Crowley, David; Rosa, André Henrique [UNESP] (My University, 2014)
The use of fertilizers with slow releasing rates in agricultural practice has proven to be a viable and sustainable practice to increase the efficiency of nutrient elements assimilation by crop plants. In this context, the present study is based on the preparation, characterization, and performance evaluation of polymeric alginate microspheres, or beads, containing biochar for the immobilization and slow release of orthophosphate. To achieve this objective, biochar was prepared from the pyrolysis of sugarcane bagasse at different temperatures (300 - 700 °C) under nitrogen atmosphere. The biochar material and three kinds of microspheres (with biochar, phosphorus and alginate; alginate and phosphorus; only alginate) were analysed by FT-IR to identify the functional groups present. The results show changes in the functional groups in biochar and a difficulty to characterize the microspheres by this method. The quantification of the phosphate ions release over time, from microspheres containing biochar, was evaluated by comparing the control experiments, without biochar, using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES). It was found that microspheres with biochar and phosphorus had a higher releasing rate, twice than those without biochar. Besides being a good procedure to provide nutrients to plant, the microsphere system can also be an excellent water resource to the plant and a good restorer of the soil pH when it is acid. Then, these preliminary results open a new multidisciplinary perspective for the use of biochar, and suggest opportunities for incorporation of biochar into slow releasing fertilizers, that may enable the usage of smaller amounts of fertilizers and improve the fertilizer efficiency.